تقييم مستويات بعض العناصر في عينات مياه جوفية من آبار محلية – دراسة مقارنة بالمعايير الدولية لمياه الشرب (Comprehensive Journal of Science, 2025)
This study aims to evaluate the quality of groundwater in the city of Sorman, western Libya, by analyzing the concentrations of some dissolved chemical elements through five parameters to calculate the water quality index (calcium, magnesium, total dissolved salts, chloride, and pH). 12 samples were collected from groundwater wells from different areas at varying depths during the period from spring 2025 AD. Analyzed using certified laboratory techniques. The results showed that most of the samples contain concentrations that exceed the permissible limits according to the standard specifications for drinking water (WQI) and the guideline values of the World Health Organization (WHO), which indicates the presence of potential health risks if water is consumed without treatment. The study recommends the necessity of periodically monitoring the quality of groundwater, and applying appropriate purification techniques to ensure the safety of the water provided to citizens.
Keywords: drinking water quality, groundwater, physicochemical parameters, surman ground water, Libyan standards, WHO.